Efektivitas Penggunaan ECourt sebagai Bentuk Pelayanan Berbasis Elektronik di Pengadilan Negeri Magetan - Sutra Dwi Nurhandayani; Ellectrananda Anugerah Ash-Shidiqqi (Jurnal Hukum Lex Generalis, 2026)
This research examines the effectiveness of e-court implementation as an electronic judicial service at the Magetan District Court, employing an empirical legal research method with statutory and sociological approaches, complemented by interview data, observations and literature studies. The findings indicate that e-court enhances accessibility, accelerates service delivery and reduces litigation costs. However, its effectiveness remains sub-optimal due to a high dependence on Legal Aid Post (Posbakum) officers and low digital literacy among the public. This study recommends the reinforcement of technology socialization and the formulation of more structured service standards to support a simple, speedy and low-cost judicial system.